2020
DOI: 10.3390/agronomy10030392
|View full text |Cite
|
Sign up to set email alerts
|

Forage Legume Establishment under Exposure to Progressive Declines in Aminocyclopyrachlor and Aminopyralid in Temperate Pastures

Abstract: Legumes such as alfalfa (Medicago sativa L.) and white clover (Trifolium repens L.) increase forage productivity and quality in northern temperate pastures, but require re-establishment following broadleaf weed control using herbicides. To quantify the residual effects of two herbicides (aminocyclopyrachlor and aminopyralid) on potential legume re-establishment we examined alfalfa and clover recruitment at two field sites over two years. Sites were over-seeded with alfalfa and clover to populate the seed bank,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…When considering fall versus spring herbicide applications, producers need to consider the weed species present to determine proper application timing, but also the specific herbicide to be used. Additionally, our findings are similar to those of other authors who have reported that commonly used pasture herbicides can result in high levels of desirable forage legume injury, and even death as was observed with aminopyralid (Beeler et al 2003;Harrington et al 2014;Mikkelson and Lym 2013;Miller et al 2020), aminopyralid þ 2,4-D (Enloe et al 2014;Payne et al 2010), 2,4-D (Payne et al 2010), 2,4-D þ dicamba (Payne et al 2010), and metsulfuron (Payne et al 2010. ) Although herbicides that contain florpyrauxifen-benzyl did significantly injure established white clover, the clover was not eliminated and recovery occurred during the trial period, indicating that this herbicide may be used in pastures containing white clover.…”
Section: Research Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…When considering fall versus spring herbicide applications, producers need to consider the weed species present to determine proper application timing, but also the specific herbicide to be used. Additionally, our findings are similar to those of other authors who have reported that commonly used pasture herbicides can result in high levels of desirable forage legume injury, and even death as was observed with aminopyralid (Beeler et al 2003;Harrington et al 2014;Mikkelson and Lym 2013;Miller et al 2020), aminopyralid þ 2,4-D (Enloe et al 2014;Payne et al 2010), 2,4-D (Payne et al 2010), 2,4-D þ dicamba (Payne et al 2010), and metsulfuron (Payne et al 2010. ) Although herbicides that contain florpyrauxifen-benzyl did significantly injure established white clover, the clover was not eliminated and recovery occurred during the trial period, indicating that this herbicide may be used in pastures containing white clover.…”
Section: Research Implicationssupporting
confidence: 92%
“…Another management concern when using herbicides is the elimination of desirable forage legumes such as white clover. Many common and widely available herbicides are frequently used to control broadleaf weeds in pastures and hayfields; however, the majority of these herbicides also kill desirable forage legumes (Beeler et al 2003;Miller et al 2020;Payne et al 2010). Forage legumes in pastures, including white clover, have several benefits such as increased forage quality (Posler et al 1993), which can ultimately lead to increases in livestock performance (Burns et al 1973).…”
Section: Introductionmentioning
confidence: 99%